Central Nervous System Non-Von Hippel-Lindau (VHL) Hemangioblastoma Evolving to Dissemination: Is Anti-Angiogenic Therapy an Option? - Cuccarini, Valeria; Tringali, Giovanni; Anghileri, Elena (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Leptomeningeal dissemination of hemangioblastomas (HB) of the central nervous system (CNS) is very rare. Few studies have reported leptomeningeal involvement in sporadic HB or in HB associated with von Hippel-Lindau (VHL) syndrome. Due to the rarity, no standard of care exists yet. Materials and Methods: A case report is described including clinical, radiological and therapeutic details. From the disease onset, the follow-up continued till death. Results: An adult man developed leptomeningeal dissemination of non-VHL HB starting from original cerebellar site. The initial lesion was removed by surgery; however 10 years later multiple supra- and subtentorial tumoral nodules showed up. Combined treatments with surgery and radiotherapy and radiosurgery were used. After short-term stability, HB progressed to spinal cord and dissemination pattern took advance. Contextually he developed neurological deterioration and polycythemia. Thus, we decided to propose to the patient the use of bevacizumab (BEV), a humanized monoclonal antibody targeting vascular endothelial growth factor (VEGF): the patient experienced 1-year stable disease, with early clinical improvement. After 5 years from the diagnosis of dissemination the patient died due to disease progression. Discussion: Leptomeningeal dissemination of HB is extremely rare within the setting of non-VHL. Based on hypervascularized biology of HB, BEV could hypothetically represent a therapeutic option. We describe an adult sporadic HB with CNS dissemination, showing a temporary stabilization of disease during BEV, improving the secondary polycythemia and exhibiting no adverse effects. Such treatment should be considered in this setting of such patient.